Implementation of wide area protection system (WAPS) for electrical power system smart transmission grids - Tetteh, Bright (Department of Electrical Engineering, 2021)
The planning, operation and control of the power system has been evolving since its inception. These changes are due to the advancement in science and technology, and changes in energy policy and customer demands. The envisioned power system - smart grid (SG) - is expected to have functional and operational capabilities that maximize the reliability, minimize generation deficit, and cost issues in the power system. However, many power systems in the world today still operate traditionally, with one-way communication and one-way power flow. Transitioning to a smart grid influences the protection schemes of the power system, as the smart grid is to leverage distributed energy resources (DERs) using distributed generation (DG) units and allow for bi-directional flow of power and information. Therefore, there is a need for advanced protection schemes. Wide-area protection (WAP) techniques are proposed as one of the solutions to solve the protection challenges in the smart grid due to their reliance on wide-area information instead of local information. This dissertation considered three WAP techniques which are differentiated based on the data used for faulted zone detection: (A) Positive sequence voltage magnitude (PSVM), (B) Gain in momentum (GIM) and (C) Sum of positive and zero sequence currents (SPZSC). The dissertation investigated their performances in terms of accuracy in detecting the faulted zones and the faulted lines, and fault clearing time. The investigation was done using three simulation platforms: MATLAB/Simulink, Real-Time (Software in the Loop (SIL)) and Hardware-in-the-Loop (HIL) implementation using Opal-RT and SEL-351A relay. The results show that, in terms of detecting the faulted zones, all the techniques investigated have 100% accuracy in all the 36 tested fault cases. However, in terms of identifying the faulted line in the faulted zone, the algorithms were not able to detect all the 36 tested cases accurately. In some cases, the adjacent line was detected instead of the actual faulted line. In those scenarios, the detected line and the faulted line present similar characteristics making the algorithms to detect the wrong line. For the faulted line detection accuracy, the algorithm (A) has an accuracy of 86%, (B) has an accuracy of 94% and (C) has an accuracy of 92%. The fault clearing times of the algorithms were similar for both the MATLAB/Simulink and realtime simulation without the actual control hardware which was the SEL-351A relay. When the simulation was done with the control hardware through Hardware-in-the-loop, a communication delay was introduced which increased the fault clearing times. The maximum fault clearing time for the techniques investigated through the HIL simulation are 404 ms, 256 ms, and 150 ms for the techniques (A), (B) and (C) respectively and this variation is due to the different fault detection methods used in the three algorithms. The fault clearing time includes communication between the Opal-RT real-time simulator and SEL-351A relay using RJ45 ethernet cable, these fault clearing times can change if a different communication medium is used. From the performance data presented, it is evident that these algorithms will perform better when used as backup protection since the common timer settings for backup protection schemes range from 1200 ms to 1800 ms, while primary protection is expected to respond almost instantaneously, that is, with no initial time delay.